Analysis of Learning Media Needs for Rounding and Assessment Materials with Character Strengthening in Grade IV of Elementary School - Rahmasari, Feby Dwi; Yuniawatika, Yuniawatika; Mas’ula, Siti (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2025)
The delivery of information or messages that are important in learning can be channeled through learning media. Along with utilizing textbooks, the learning process can be further supported by employing a learning message agent. Creating effective learning tools can help address challenges students face, particularly in mathematics education. This study aims to examine the requirements for mathematics learning media to simplify the comprehension of the material for students. The participants in this study included teachers and all grade IV students at UPT SDN Sumberjati, totaling 13 students. Data was collected via interviews and questionnaires, highlighting the need for engaging, practical learning tools that include images and videos focused on rounding, estimation, and character development.